Christianity, gender and self-care : conversations with university students about coping with social isolation during COVID-19 - Chew, Jeremy Jia En (Nanyang Technological University, 2021)
The COVID-19 pandemic has shown us how religiosity is an effective coping mechanism to alleviate the stress of social isolation. This sociological study uses a Transactional Stress Process Model to investigate how masculinity affects the receptiveness of religious individuals towards practicing self-care. In-depth interviews regarding experiences during Singapore’s Circuit Breaker lockdown and Biblical beliefs about masculinity and self-care were conducted amongst a convenience sample of 10 university-going Christian males. Findings showed that they identified with examples of expressive masculinity found in Scripture. This shared belief translated into a receptiveness towards adopting ‘Christianized’ rituals of self-care called ‘rest’. I discuss the theoretical implications of such a practice in the context of a globalized, neoliberal, and social media-saturated world. Practical recommendations for the local Christian community hinge upon whether the uncritical acceptance of self-care may weaken its future leaders’ convictions in laying down one’s life for Jesus and His church.